Epoxy Composite with Milimetric Carbon Nanotubes - Antunes, E. F.; Edwards, E. R. [UNESP]; Botelho, Edson Cocchieri [UNESP]; Costa, M. L. [UNESP]; Corat, E. J.; Massi, M. (Amer Scientific Publishers, 2011)
Composite of multi-walled carbon nanotubes (MWCNT) and epoxy resin DGEBA were obtained with DDM hardener. The MWCNT were synthesized with length of millimeters by camphor/ferrocene pyrolysis. Different cure temperatures of DGEBA/DDM with addition of up to 1% MWCNT were studied to evaluate eventual changes in cure kinetics by differential scanning calorimetry (DSC). No change was detected in glass transition temperature with insertion of MWCNT although the cure enthalpy has been reduced.
Keywords: MWCNT; Epoxy; DGEBA; DDM; Cure; T(g)